Planning to meet future water needs - Hargreaves, George H., author; Olsen, Eric R., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Conservative projections foresee world population growing from approximately six billion to over eight billion people by 2050. During that same period, per capita food grain production, irrigated area, and the income of the poorest 20% are expected to decline. As a result, much of the world's population faces a future of poverty and hunger. These people, forced to the economic margins, often engage in harmful agricultural practices-fanning steep slopes, slash-burn agriculture, overgrazing-which increase soil erosion and flooding. In the context of growing population and poverty, this paper discusses several water-related issues: irrigation, depletion of groundwater, drainage, and flood control. Also discussed are the roles of government and the private sector in water resource management. Finally, it discusses the question of resource conservation or development, concluding that before conservation becomes a viable choice (especially for the poor), development is necessary. To help plan sound water projects in the future, this paper advocates the development of a global water resource inventory. It describes a start toward such an inventory-the IWMI "World Water and Climate Atlas"-and how it can be used.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.